Pink Concrete - Curr, Jill Alexandra (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
(From Reader Report Reflection) - I started this course believing I was not a writer. I knew that I loved to write, I knew that it was innate to how I perceived the world. I had written a novel previously, it was an outpouring, uncontrollable imagination spew. I was often scared and doubted myself throughout writing it, but I took comfort in my reading. I picked up all the classics, modern and old, rewriting the words into notebooks alongside my own, retracing the sounds, the rhythms, the symbols and their little links, the pauses. I collected pieces rereading them with reverence, my fingers curling over the lines sunken into the page. I didn't understand what I was doing, it felt natural to hide in the skirts of other writers peering behind the curtain to see how they built the illusion. And yet, even after finishing my novel I still didn't think I was a writer; it was a hobby, it was something extra to me, a backpack I could take off and on. I denied what was innate, and said it was not that important to me. I applied for this Master's in Creative Writing (MACW)7 course because I wanted external validation on my first novel and an application was probably the only way, I was going to get someone to read it. It is sad and stunted that I needed this external validation to believe I could try, to believe that I could learn to control this compulsion, to believe that I could become a writer. In our first course contact week,8 lecturers and supervisors kept saying again again that we were already writers, that this is what we are. I was scared of this, that they would find out I was not really meant to be here. Writing, taking those solitary thoughts that are too much for my skull and making them real, something tangible; this is how I move through my existence. I take pieces of myself and paste them to the page, otherwise the thoughts build up like snow around a car until you are suffocating in an icebox. And by removing this part of myself to just a hobby, a silly backpack that I can pick up and put down, was just me running away. This MACW course gave me the tools to tap into what I am, that I have a why that I must write to and that I have an audience for this why. By sharing pieces of myself, I make them real again, something I can study, tracing their edges, their dark underbelly, the light hillocks. I sat with my fear for two years slowly, piece by piece, cracking it open. I learnt to love my voice and believe in it without needing external validation, without needing the gold star of acceptance, because I accept and love what I am trying to build with my writing.
Keywords: Creative writing (Higher education) -- South Africa; Diaries -- Authorship; South African fiction (English) 21st century; English fiction History and criticism; Nigerian fiction (English) History and criticism; Argentine fiction History and criticism; Angolan fiction (Portuguese) History and criticism